Investigating mobile broadband adoption and usage: S case of smartphone in Sweden - Chatchai Kongaut; Erik Bohlin (International Telecommunications Society (ITS), 2014)
Looking back at the last decade, the mobile phone has been greatly developed from only voice call and text message to a multi-purpose device, including camera, music player, games, and even small computer. The development of internet features in mobile phones has also continuously and extensively changed from providing only limited internet browsing in the early 2000s to watching high quality video on demand nowadays. The speed of internet is also significantly increased since the introduction of smartphones. After the implementation of 3G networks in the last decade and recently the LTE networks of 4G technology in the last few years, the transmission speed of mobile internet supports the use of mobile phones to be able to provide high-speed internet services which is called mobile broadband. Furthermore, recent studies have also suggested that mobile broadband positively affect economic outputs (see Thompson Jr. and Garbacz, 2011) as well as reduce the digital divide problem, especially in the rural where fixed broadband infrastructure is limited or not available (see Srinuan, C. et al., 2012 and Prieger, 2013). With a number of possible benefits from mobile internet/broadband, it is interesting to analyse how mobile internet adoption has developed in the last decade and what factors are currently determining mobile broadband adoption in this current stage where smartphones are highly developed and transmission speed is much improved. To understand an adoption and a usage of one service, the case study of one country is more suitable than a cross-country analysis. In this paper, Sweden is selected as a case study for representing a developed country with well-developed mobile and broadband services. The method of this paper is applying bivariate probit with sample selection since the dataset consist of two sets of binary outcomes (adoption and usage). The data used in this paper is mainly based on the annual questionnaire conducted by the Swedish Post and Telecom Authority (PTS) in 2013.
Keywords: 330; mobile broadband; mobile diffusion; mobile adoption; Sweden